Body Tactile Stimulation Reduces the Effects of High Stocking Density on the Welfare of Nile Tilapia (Oreochromis niloticus) - Gauy, Ana Carolina dos Santos [UNESP]; Bolognesi, Marcela Cesar [UNESP]; Gonçalves-de-Freitas, Eliane [UNESP] (MDPI, 2023)
High stocking density is used in aquaculture to optimize farming. However, such strategies can stress territorial fish by increasing aggression, thus harming the fish welfare and productive performance. Here, we tested the effect of long-term tactile body stimulation (TS) on alleviating the impact of high stocking density in Nile tilapia (Oreochromis niloticus). Ten males were grouped for 21 days into four treatments (10 replicates each one) combining TS with high (1.2 kg·m³) or low (0.6 kg·m³) densities: (1) without TS and high density; (2) without TS and low density; (3) with TS and high density; and (4) with TS and low density. A rectangular PVC frame fitted with vertical plastic sticks sided with silicone bristles was placed in the center of aquarium. The fish receive TS when passing through the bristles. An apparatus without bristles was used as control. We found higher cortisol levels under TS conditions. All parameters of productive performance (growth, food efficiency, and condition factor) were higher in the treatment with TS and low density, lower in the treatment without TS and high density, and similar between treatments high density with TS and low density without TS. The results suggest that TS improves productive performance of Nile tilapia, counteracting the negative effects of high stocking density.
Keywords: food efficiency; growth rate; sensorial enrichment; stress; welfare